MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP DENGAN PENDEKATAN KONTEKSTUAL MELALUI PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION - Khairunisa, Shabrina; Anita, Ika Wahyu; Sugandi, Asep Ikin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research examines the learning of mathematics-learning cooperatives the type of Team Assisted Individualization with contextual approach and it is relation with improved mathematical connection quality of high school (Junior High School) Private in the city of Bandung. The purpose of this research was: know how to increasiing learner mathematical connection quality who follow the method of contextual approach Through Cooperative Learning the Type of TAI compared with students who follow the teaching of mathematics with the conventional models, implementation approach contextual approach in class and the difficulties faced students of middle school in solving about the connection mathematics. The study instrument apply was a black-and-white exam mathematical connection quality. The results obtained in the form of the pretest and posttest scores then processed with statistical methods test the difference of two averages. The output indicate that improvement of connection quality of middle school student who follow the method of contextual approach Through Cooperative Learning the Type of TAI is more increased compared with students who follow the teaching of mathematics with the conventional models. Implementation contextual approach can improve the ability of connection mathematics students middle school, the difficulties faced students middle school in solving about the connection mathematics is indicator using math in the part of another study or in daily life.